Nanoparticle-Enhanced 3D-Connector Microfluidic Paper-Based Analytical Device (3D-µPADs) for Sensitive and Cost-Effective Detection of Albumin-Creatinine Ratio in Urine Sample - Sabarudin, Akhmad; Fiddaroini, Saidun; Fahmi, Ahmad Luthfi; Roja’i, Abdul Munir; Salsabila, Isadora Evani; Aulanni’am; Srihardyastutie, Arie; Susanti, Hani; Samsu, Nur (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Chronic kidney disease (CKD) is a global health challenge affecting over 800 million people worldwide. Early detection is crucial to prevent progression to end-stage renal disease (ESRD), where life-saving interventions like dialysis or transplantation are necessary. Among the markers for early kidney damage, the Albumin Creatinine Ratio (ACR) in urine is one of the most reliable. Conventional methods of ACR detection, such as LC/MS-MS and ELISA, are highly accurate but require expensive equipment and skilled personnel, limiting their accessibility, especially in resource-limited settings. To address this, we developed a 3D-connector microfluidic paperbased analytical device (3D-µPADs) enhanced with gold nanoparticles (AuNPs) for sensitive and low-cost ACR detection. The integration of AuNPs amplifies colorimetric signals, enhancing the visual distinction in albumin detection. Our 3D-µPADs werefabricated using chromatographic paper Whatman No. 1 with hydrophobic barriers created by solid wax printing, followed by reagent immobilization for albumin and creatinine detection. The colorimetric and distance responses, based on reactions with Bromocresol Green (BCG) and Chrome Azurol S-Palladium (CAS-Pd2+), were analyzed using ImageJ software to quantify albumin and creatinine levels. The 3D-µPADs exhibited optimal sensitivity and accuracy, with linear detection ranges for albumin and creatinine of 30–400 mg/g. Validation with human urine samples demonstrated an accuracy of 93.04%, suggesting that 3D-µPADs offer a promising alternative for early nephropathy detection. Our findings provide a cost-effective, accessible tool for CKD screening, potentially transforming diagnostics in low-resource environments.